Bis(σ-B-H) complexes of copper(i): precursors to a heterogeneous amine-borane dehydrogenation catalyst - Nako,AE; White,AJ; Crimmin,MR (Dalton Transactions, 2015)
A series of bis(σ-B-H) complexes of copper(i) have been prepared by displacement of arene solvent from a β-diketiminate copper(i) complex by four-coordinate boranes, H3B-L (L = NMe3, lutidine). In the presence of the same copper arene complex, the secondary amine-borane H3B-NMe2H undergoes dehydrogenation. We provide evidence for formation of a heterogengous catalyst from decomposition of the solution species.